.5(x+2)=3x-5(3-x)-8

Simple and best practice solution for .5(x+2)=3x-5(3-x)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5(x+2)=3x-5(3-x)-8 equation:


Simplifying
0.5(x + 2) = 3x + -5(3 + -1x) + -8

Reorder the terms:
0.5(2 + x) = 3x + -5(3 + -1x) + -8
(2 * 0.5 + x * 0.5) = 3x + -5(3 + -1x) + -8
(1 + 0.5x) = 3x + -5(3 + -1x) + -8
1 + 0.5x = 3x + (3 * -5 + -1x * -5) + -8
1 + 0.5x = 3x + (-15 + 5x) + -8

Reorder the terms:
1 + 0.5x = -15 + -8 + 3x + 5x

Combine like terms: -15 + -8 = -23
1 + 0.5x = -23 + 3x + 5x

Combine like terms: 3x + 5x = 8x
1 + 0.5x = -23 + 8x

Solving
1 + 0.5x = -23 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
1 + 0.5x + -8x = -23 + 8x + -8x

Combine like terms: 0.5x + -8x = -7.5x
1 + -7.5x = -23 + 8x + -8x

Combine like terms: 8x + -8x = 0
1 + -7.5x = -23 + 0
1 + -7.5x = -23

Add '-1' to each side of the equation.
1 + -1 + -7.5x = -23 + -1

Combine like terms: 1 + -1 = 0
0 + -7.5x = -23 + -1
-7.5x = -23 + -1

Combine like terms: -23 + -1 = -24
-7.5x = -24

Divide each side by '-7.5'.
x = 3.2

Simplifying
x = 3.2

See similar equations:

| -72+6v=-4 | | .4(4x+11)=4(1-3x)+14 | | -3/2v-4/7=-8/5 | | 2x-5+6-x-2x=17 | | 150+2p=195-1p | | (-3)+17x-6(-3)=2 | | 3(4x-5)=5(2x-1) | | x=-14+5y | | 5-x+37=50-10 | | 3a+6=-4a+2 | | 12x-21=28(4x-1) | | 12y^9/2y^11 | | 5-9/8x=6 | | X-4+4=-7 | | (y^2-x^2)dy+(2*x*y)dx=0 | | X-4+4=7 | | F(x)=-3(x+3)squared+3 | | 4+16x=10+15x | | 8x+-7=-2x+5 | | 10+3x-x-4=x | | 13x+17+34=90 | | 8x+1+9x-7=180 | | Z-6=z-4 | | -2x-7=32 | | (4+8)n=36 | | (4+8)n=3 | | 10x-14=-2x-13 | | 772x= | | 10x-14=2x+13 | | 5y+39+4x+6=180 | | x(x+2)=1295 | | 9x-15=-5x-16 |

Equations solver categories